Efficacy and safety of antifibrinolytics in oncological surgery: a systematic review and meta-analysis - Sampaio,Aline Menezes (2019)
Abstract Background and objectives: The administration of antifibrinolytics has been shown to be effective in reducing blood loss and the need for transfusions in surgeries. However, few studies have evaluated these drugs in cancer surgery. The objective was to review the efficacy and safety of the treatment with antifibrinolytics in patients who underwent oncologic surgeries. Contents: An electronic bibliographic research was conducted in PubMed, OVID, MEDLINE, EMBASE, EBSCO and in the Cochrane Library data basis in order to identify randomized clinical trials performed in any type of oncologic surgery. The data evaluated were blood loss, need for transfusion and incidence of arteriovenous thromboembolism. Five randomized controlled trials evaluating 838 patients met the inclusion requirements. In the analysis of the incidence of thromboembolic events in the five RCTs, there was no statistically significant difference between the administration of tranexamic acid when compared with the placebo (OR = 0.36, 95% IC: 0.11‒1.19, p= 0.09, I2 = 0%). However, when total estimated blood loss and need for blood transfusion are analyzed, the use of tranexamic acid was associated with a significant reduction over placebo (MD = −135.79, 95% CI: −179.50 to −92.08, p< 0.00001, I2= 68%) and (OR = 0.45, 95% CI: 0.32‒0.65, p< 0.00001, I2= 60%), respectively. Conclusions: This meta-analysis found no evidence that the administration of antifibrinolytics increases the risk of thromboembolic complications in patients submitted to oncologic surgery, and has shown evidence that it is effective in reducing total perioperative blood loss and the need for blood transfusion.